Narrativas do itinerário escolar de professoras negras e suas implicações na práxis pedagógica - Conceição, Marcio Santos da (2013)
This paper aims to reflect on the importance of (self) biographical method for teacher training. Based on the works of authors such as Souza, Josso and Nóvoa, among others, it seeks to discuss the relevance found in the training work based on Life Stories which appreciates the subjectivity and uniqueness of these stories in contrast to a Cartesian teacher training model, in which the teacher is a mere transmitter of knowledge and does not feel themselves as the actors of their own training. The discussions are also guided by the attempt to understand how the journey of two black school teachers of a Quilombola community guides and directs their pedagogical praxis. In this paradigm shift, it is let behind a formative model centered in what some authors call technical rationality and subjectivity (s) is encouraged, because it is believed that there is no teaching without learning and vice versa. This is a survey of an ethnographical type with a qualitative approach.